2020
DOI: 10.3390/nu12030800
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life: Psychological Symptoms—Effects of a 2-Month Healthy Diet and Nutraceutical Intervention; A Randomized, Open-Label Intervention Trial (RISTOMED)

Abstract: Depression symptoms and lower health-related quality of life (HRQoL) are associated with inflammation. This multicenter dietary intervention was shown to reduce inflammation in older people. This was the main outcome. Here, we describe the effects on HRQoL, anxiety, and depressive symptoms according to inflammation status. Overall, 125 healthy older subjects (65–80 year) were recruited (Italy, France, and Germany) and randomized into four arms (A, Healthy diet (HD); B, HD plus De Simone Formulation probiotic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In addition, in order to increase the homogeneity of the included studies, we only included studies with a placebo control. Three randomized studies conducted in healthy elderly utilized a diet group as the control and lacked a true placebo control; therefore, we did not include these studies [ 100 , 101 , 102 ]. In addition, Meance et al and Matsumoto et al also lacked placebo controls and were excluded [ 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in order to increase the homogeneity of the included studies, we only included studies with a placebo control. Three randomized studies conducted in healthy elderly utilized a diet group as the control and lacked a true placebo control; therefore, we did not include these studies [ 100 , 101 , 102 ]. In addition, Meance et al and Matsumoto et al also lacked placebo controls and were excluded [ 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RISTOMED (an internet-based project initiated for the elderly to prevent gut disturbances) study evaluated the effect of inflammation status on health-related quality of life, symptoms of anxiety, and depression in a healthy older population, as compared to group A (healthy diet), group B (probiotic with a healthy diet), group C (healthy diet plus monoterpene), and group D (healthy diet plus argan oil). The study reported a decrease in depressive symptoms in all four groups, which is attributable to a healthy diet, but found no associations between inflammation status and anxiety and depressive symptoms [ 51 ]. Another study suggested PROVIT (probiotics and vitamins) as an efficient adjunct therapy that could decrease inflammation and manage symptoms based on reductions in depression scores and IL-6 gene expression levels [ 52 ].…”
Section: Reviewmentioning
confidence: 99%